Characterization of Minor Millets (Panicum sumatrense and Eleusine coracana) for Trait Related to Moisture Stress Tolerance - H., Patil Arun; Dubey, Mahima; Sao, Abhinav; Chandel, Girish (International Journal of Bio-resource and Stress Management, 2018)
Drought stress is one of the abiotic stresses which may alter plant growth, metabolism and yield. Water stress limits the growth, productivity and quality of agricultural crops in the world. Water Stress is not only due to the scarcity of water but also due other factors such as salinity, high temperatures and severe cold that make plants not able to absorb enough water from soil to grow well and this is called physiological drought that leads to a series of disorders in physiological and biochemical processes. Millets are resilient to extreme environmental conditions especially to inadequate moisture and are rich in nutrients. The aim of this research was to analyze the effects of water stress on relative water content, proline, soluble carbohydrates and chlorophyll content of minor millet genotypes under control conditions. The photosynthetic pigments like chlorophyll a, chlorophyll b and total chlorophyll decreased and the biochemical components like, proline, leaf protein and carbohydrate increased under water stress. In this study little millet genotypes showed minimum decrease in chlorophyll content and maximum increase in proline, protein and carbohydrate content when compared to the previously reported tolerant millet genotype. This study suggested the little millet (Panicum sumatrense) genotype RLM 37 having drought tolerant adaptive mechanism and better performance under water stress.